Engineered Zinc Finger Protein Targeting 2LTR Inhibits HIV Integration in Hematopoietic Stem and Progenitor Cell-Derived Macrophages: In Vitro Study - Koollawat Chupradit; Wannisa Khamaikawin; Supachai Sakkhachornphop; Chaniporn Puaninta; Bruce E. Torbett; Suparerk Borwornpinyo; Suradej Hongeng; Methichit Wattanapanitch; Chatchai Tayapiwatana (My University, 2022)
Human hematopoietic stem/progenitor cell (HSPC)-based gene therapy is a promising direction for curing HIV-1-infected individuals. The zinc finger protein (2LTRZFP) designed to target the 2-LTR-circle junction of HIV-1 cDNA was previously reported as an intracellular antiviral molecular scaffold that prevents HIV integration. Here, we elucidate the efficacy and safety of using 2LTRZFP in human CD34+ HSPCs. We transduced 2LTRZFP which has the mCherry tag (2LTRZFPmCherry) into human CD34+ HSPCs using a lentiviral vector. The 2LTRZFPmCherry-transduced HSPCs were subsequently differentiated into macrophages. The expression levels of pro-apoptotic proteins of the 2LTRZFPmCherry-transduced HSPCs showed no significant difference from those of the non-transduced control. Furthermore, the 2LTRZFPmCherry-transduced HSPCs were successfully differentiated into mature macrophages, which had normal phagocytic function. The cytokine secretion assay demonstrated that 2LTRZFPmCherry-transduced CD34+ derived macrophages promoted the polarization towards classically activated (M1) subtypes. More importantly, the 2LTRZFPmCherry transduced cells significantly exhibited resistance to HIV-1 integration in vitro. Our findings demonstrate that the 2LTRZFPmCherry-transduced macrophages were found to be functionally and phenotypically normal, with no adverse effects of the anti-HIV-1 scaffold. Our data suggest that the anti-HIV-1 integrase scaffold is a promising antiviral molecule that could be applied to human CD34+ HSPC-based gene therapy for AIDS patients.
Keywords: HIV Research and Treatment